- #1

- 63

- 0

## Homework Statement

Prove that sin

^{6}+ cos

^{6}= 1 - 3sin

^{2}cos

^{2}

## Homework Equations

(1)

## The Attempt at a Solution

I tried to convert those all in terms of sine and cosine only but it didn't work.

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter acen_gr
- Start date

- #1

- 63

- 0

Prove that sin

(1)

I tried to convert those all in terms of sine and cosine only but it didn't work.

- #2

Mentallic

Homework Helper

- 3,798

- 94

## Homework Statement

Prove that sin^{6}+ cos^{6}= 1 - 3sin^{2}cos^{2}

## Homework Equations

(1)

## The Attempt at a Solution

I tried to convert those all in terms of sine and cosine only but it didn't work.

Notice that [itex]\sin^6x=\left(\sin^2x\right)^3[/itex] and that [itex]\sin^2x=1-\cos^2x[/itex]

Start by trying to apply these two ideas to the LHS of the equation.

- #3

- 63

- 0

sin

(sin

(1 - cos

1 - 3cos

1 - 3cos

1 - 3cos

1 - 3cos

1 - 3cos

1 - 3cos

- #4

Mentallic

Homework Helper

- 3,798

- 94

Every step is mathematically equivalent to its preceding step (so you haven't broken any rules) so yes, it's rightThis is my work. Is this right?

If I'm to be a bit picky however, I'll mention that it's not necessary to write ... = RHS on every line. You should instead set out your proof as so:

LHS = ...

= ...

= ...

= RHS

You don't need to keep writing LHS either, unless you make any manipulations to both sides of the equality such as:

LHS = ...

LHS + 1 = ... + 1

Although you shouldn't do this when trying to prove LHS = RHS. If you needed to add 1 to the RHS then you can minus one to keep it balanced as so:

LHS = ...

= ... + 1 - 1

I'd also skip this line altogether (unless it's to help you to personally keep track of things and not get confused), but if not, you should just go ahead and factorize straight away:1 - 3cos^{2}x + 3(cos^{2}x)(cos^{2}x) = RHS

[tex]=1-3\cos^2x+3cos^4x[/tex]

[tex]=1-3\cos^2x(1-cos^2x)[/tex]

Also this last line is unnecessary, but there's no harm done if you feel like doing it.1 - 3cos^{2}x(sin^{2}x) = RHS

1 - 3cos^{2}xsin^{2}x = 1 - 3sin^{2}xcos^{2}x

- #5

- 63

- 0

- #6

Mentallic

Homework Helper

- 3,798

- 94

You're welcome and that's glad to hear!

Share: